If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -8x = 11 + 6x Solving 17 + -8x = 11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 17 + -8x + -6x = 11 + 6x + -6x Combine like terms: -8x + -6x = -14x 17 + -14x = 11 + 6x + -6x Combine like terms: 6x + -6x = 0 17 + -14x = 11 + 0 17 + -14x = 11 Add '-17' to each side of the equation. 17 + -17 + -14x = 11 + -17 Combine like terms: 17 + -17 = 0 0 + -14x = 11 + -17 -14x = 11 + -17 Combine like terms: 11 + -17 = -6 -14x = -6 Divide each side by '-14'. x = 0.4285714286 Simplifying x = 0.4285714286
| t^2+3t+2=0 | | 0+15= | | 5x=(4x-2)(m+7) | | 4x(3x+5)= | | 5w-5w= | | 3=7x+10 | | 16x^2+4=36 | | 4.2x-3=1-x | | (x+2)(x-3)=(x-4)(x+5) | | -2(x-3)=2 | | 16K^2-36= | | 7a^2+13x-2= | | 5m=17 | | 5x^2-22=-10x | | X^2+22x+5= | | 18+x+2x=39 | | 0=2x^4-5x^2+1 | | 5t+2(1-5t)= | | 90+x-24+x=180 | | X*2-6x-7=0 | | (25b-8)-6(4b+3)=-2 | | .5x^2-3x=-9 | | (2z+7)(9-z)=0 | | 4x-(3x+6)=0 | | (8a+7)(2a^2+7a-9)= | | 11(t-5)+7t=6(3t+3)-9 | | 2B+4B-4=20 | | 2y-8=-3y-8 | | (9y^2-7y+9)-(7y^2-7y+8)= | | 49x^2-14x=-1 | | -2(5s-6)-12=-3(8s+2)-3 | | 6x+5x+4+9=7x+4+3x |